IDENTIFIKASI DEOKSIPIRIDINOLIN PADA SALIVA WANITA USIA PERIMENOPAUSE - Nanda Afnita; Muhammad Nurul Amin; Agustin Wulan Suci D (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2014)
Perimenopause is trantition phase of nomal ovulation cicle to menopause that signed decreasingestrogen hormone production. In this phase, women will be physiology and psychology alteration related fluctuationof estrogen hormone. The estrogen level alteration is one of cause reducing of bone density in perimenopausewomen. When estrogen level decreases, it will induce osteoclast activity and finally cause bone resorption. In boneresorption osteoclast secretes protease that can dissolve collagen which is in organic matrix and free bone mineral.Mature collagen is bound by pyridinium crosslink that it will be degraded in bone resorption process, such asdeoxypyridinoline. Deoxypyridinoline have suggested as collagen degradtion marker of bone resorption in serumand urine. This study was objective to identify deoxypyridinoline in saliva of perimenopause women. The subjects ofthis study were perimenopause women who were 40-55 years old. The subjects had to fulfill informed consent and beundergone intra oral examination, including caries and periodontal index index. After that the subjects collectedtheir whole saliva. Deoxypyridinoline in saliva was identified by Liquid chromatography Mass Spectroscopy. The resultshowed that deoxypyridinoline level of perimenopause women was about 23.802 ppm. This level was higher thanproductive women. The conclusion was deoxypyridinoline level in saliva of permenopause women